KUAT GESER LANGSUNG BETON AGREGAT DAUR ULANG DARI BATA RINGAN - Suseno, Hadi; Suharwanto, Suharwanto; Komarudin, Komarudin (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Waste materials in construction projects are often found, one of which is light brick waste,This study aims to determine the differences in the shear strength of normal concrete and recycled concrete with lightweight brick crushed aggregate, lightweight brick coarse aggregate used in this study with a mixture of 0% 50% and 100% lightweight brick as a substitute for coarse aggregate, with test objects in the form of S with an immersion period of 28 days and a planned concrete quality of 10 MPa, 15 MPa and 19 MPa. Shear strength obtained in concrete quality 10 MPa 0% lightweight brick 2.00 Nmm, 50% lightweight brick 1.19 Nmm, 100% lightweight brick 0.89 Nmm in concrete quality 15 MPa 0% lightweight brick 3.04 Nmm, 50% lightweight brick 1.26 Nmm, 100% lightweight brick 1.19 Nmm and at 19 Mpa quality 0% lightweight brick 3.26 Nmm 50% lightweight brick 1.88 Nmm, 100% lightweight brick 1.13 Nmm, shear strength the mixture of 50% and 100% lightweight bricks experienced a decrease in shear strength due to the wear and tear of the lightweight brick aggregate which was high enough to affect the quality strength of the concrete.